Bioerosion on rudist shells from the Upper Cretaceous of Cuba: Paleobiological, paleoecological and taphonomic implications. (January 2022) - Villegas-Martín, Jorge; Rojas-Consuegra, Reinaldo; Verde, Mariano; Belaústegui, Zain; Ritter, Matias; Horodyski, Rodrigo Scalise
Abstract: The fossil record of bioerosion on rudists is commonly restricted to brief mentions that mainly use general terms and do not constitute detailed ichnological studies. This contribution comprises a detailed study of the bioerosion structures present on the shells of different species of rudists from the Upper Cretaceous (Campanian-Maastrichtian) of Cuba. In addition, paleobiological, paleoecological and taphonomic implications of these boring are inferred. Among the studied material, seventeen rudist shells exhibits bioerosion structures. Based on their morphological features the borings have been ascribed to Gastrochaenolites isp. and Entobia isp. Gastrochaenid bivalves and clionaid sponges, respectively, have been proposed as their more likely producers. The modes of occurrence, density, and position of such bioerosion structures rule out a syn-vivo relationship between rudists and boring bivalves and sponges, demonstrating that colonization mainly was postmortem. Furthermore, the combination of these data together with previous paleoecological interpretations and the fact that the most parts of the rudist shells are filled by sediment, provides enough evidence to propose a subsequent process of reworking and reburial of these shells in shallow marine settings. Highlights: Gastrochaenolites and Entobia are describe in post-mortem rudist shells. Borings are assigned to the activity of boring bivalves and clionid sponges. Characteristics of the borings suggest several events of colonization of the shells. Rudist shells worked as benthic islands for colonization by boring bivalves. Bioerosion occurred in shallow marine conditions.